Faunal deposits and displays in the early Neolithic, new evidence from Ganj Dareh, central Zagros - Bangsgaard , Pernille; Yeomans , Lisa; Darabi , Hojjat; Richter , Tobias (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2024)
The relationship between animals and humans underwent a significant transformation during the transition from hunting and gathering to agriculture and domestication in southwest Asia. These changes were not only economic but also cultural and symbolic. Display and deliberate deposition of animal parts inside settlements and individual buildings highlights this changing relationship. Here we report recently acquired evidence from the aceramic Neolithic site of Ganj Dareh, Iran, that showcases the use of animal parts in display and deposition. These faunal deposits contained both birds and mammals represented by varying body parts and in different combinations. The circumstances of deposition also vary considerably suggesting a difference in visibility. This new evidence strengthens views that display and ritualised activities were important as human society was in the process of adapting agricultural subsistence strategies, and negotiating human-animal relations.